SISTEM PAKAR DIAGNOSA PENYAKIT KANKER PADA ANAK MENGGUNAKAN METODE CERTAINTY FACTOR - Aan Sugianto; Sumiati Sumiati (Universitas Serang Raya, 2016)
Kanker can happen to anyone regardless of age groups, including children, then the parents need to know the disease early on. According to data from the World Health Organization (WHO) kanker patients every year in the world to be 6.25 million people, and of that number, 4 percent or 250 thousand patients are children (as per February 2011). Expert systems are computer programs that imitate the reasoning an expert with expertise in a particular area of knowledge (Turban, 1995). Expert systems try to find solutions, providing suggestions or conclusions are consistent with the problems it finds.The author managed to implement an expert system that can cope with the highest degree of confidence or certainty factor data obtained from the results of the consultation with the patient through the certainty factor method. Hope the author, this system can help doctors or people who know even less in making decisions when diagnosing kanker in children.